The Effect of Perceived Value and Sales Promotion on Repurchase Intention by Mediation of Fund User Customer Satisfaction at Supermal Lippo Karawaci Tangerang - Rahmat Taufik, Edi; Desty Ayu Lestari, Monica (British Journal of Marketing Studies, 2023)
The effect of Perceived Value and Sales Promotion on Repurchase Intention by mediating Customer Satisfaction for user of DANA in Supermal Lippo Karawaci, Tangerang. The population in this study is the user of DANA in Supermal Lippo Karawaci, Tangerang. This research sample amounted 75 the user of DANA in Supermal Lippo Karawaci, Tangerang. In this study the methode used to analysis is the non-probability sampling method with the research method used is descriptive research with a quantitative approach. Data analyze techniques used in this study are Structural Equation Modelling (SEM) with using analysis tools SmartPLS 3.0. The results of the study using SmartPLS 3.0 show that: (1) Perceived Value has a positive and significant effect on Repurchase Intention (2) Sales Promotion has a positive and significant effect on Repurchase Intention (3) Perceived Value has a positive and significant effect on Customer Satisfaction (4) Sales Promotion has a positive and significant effect on Customer Satisfaction (5) Customer Satisfaction has a positive and significant effect on Repurchase Intention.